Mal-estar na província: modernidade e nostalgia na literatura regionalista de Alcides Maya, J. Simões Lopes Neto e Roque Callage - Thesing, Neandro Vieira (2024)
This thesis addresses the concept of regionalism and writers from Rio Grande do Sul linked to this literary tradition. Three authors who produced in the 1910s and 1920s will be discussed, focusing the analysis on the works seen as their main productions: Alcides Maya, Ruínas vivas (1910); João Simões Lopes Neto, Contos gauchescos (1912) and Lendas do sul (1913); and Roque Callage, Terra gaúcha (1914). The authors will be analyzed taking into account the relationship of works and authors with the modernization process and the temporal relationships contained, using the concept of nostalgia for this. The thesis is organized into two parts. The first part is divided into two chapters, one that seeks to contextualize the debates involving the concept of regionalism in the definition of the nation, the second that addresses the concept as a discussion in literary criticism. In the second part, the three authors, the intellectual context and their corpus will be analyzed based on theoretical-methodological assumptions. Finally, it was concluded that the works of regionalism participate in the disputes over the definition of the space of experience and horizon of expectation of Rio Grande do Sul society in the period. The works of regionalisms, a plural phenomenon, indicate responses to long-term problems in the national intellectual debate, also relating to specific contexts of acceleration in the pace of modernizing transformations, and can be seen as a non-subjection to the process of modernization and defense of changes social reformists, not conservatives. Although close, each author created their own version of Gaucho regionalism, with particularities, largely due to the character of the reflective nostalgia present in their productions, in addition to common traits, such as the presence of violence and the character of the historical subjects narrated. The research is linked to the "Border, Politics and Society" Research Line of the Postgraduate Program in History at the Federal University of Santa Maria (UFSM).